CANTRIK CULTURAL ADAPTATION: STUDENT’S ROLE AS TEACHER ASSISTANT IN MAXIMIZING CLASS LEARNING PROCESS - Astrid Wangsagirindra Pudjastawa (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
In the era of the COVID-19 pandemic, a teacher is required to be responsible for his students, in terms of student achievement, health, safety, and welfare. In the learning process in the classroom, teachers are expected to minimize discrimination in the classroom and seek intensive guidance for students with special needs. In Javanese culture, cantrik is known, namely, someone who always follows the teacher; this cantrik culture is close to the term assistance in this modern era. A teacher assistant is someone who supports teacher learning in the classroom. To realize educational services that are following the abilities of each student from each group in the classroom in this era of the COVID-19 pandemic, a teacher should maximize the level of service by taking an assistant from among the students. Assistants from among students can improve student skills, self-confidence and provide a learning atmosphere based on diversity.: In the era of the COVID-19 pandemic, a teacher is required to be responsible for his students, in terms of student achievement, health, safety, and welfare. In the learning process in the classroom, teachers are expected to minimize discrimination in the classroom and seek intensive guidance for students with special needs. In Javanese culture, cantrik is known, namely, someone who always follows the teacher; this cantrik culture is close to the term assistance in this modern era. A teacher assistant is someone who supports teacher learning in the classroom. To realize educational services that are following the abilities of each student from each group in the classroom in this era of the COVID-19 pandemic, a teacher should maximize the level of service by taking an assistant from among the students. Assistants from among students can improve student skills, self-confidence and provide a learning atmosphere based on diversity.